630 PD-L1/CD47 tumor directed B-BodyTM bispecific antibodies demonstrating significant anti-tumor activity with no toxicity in preclinical models. (9th November 2020) - Kantak, Seema; Glaser, Bryan; Wetter, Justin; Sim, Bee-Cheng; Higaki, Jeff; Beal, Jacob; Ollerman, Sara; Pulukkunat, Dileep; Bawadekar, Mandar; Kaplan, Charles; Lamb, Peter; Hammer, Bonnie
Abstract : Background: Tumor cells have been shown to utilize both innate and adaptive checkpoints to evade anti-tumor immune responses. CD47 and PD-L1 are two targets widely expressed on the cell surface of tumor cells and are predicted to coordinately suppress innate and adaptive sensing respectively to evade immune control. PD-L1 dampens T cell-mediated tumor killing (via PD-L1/PD-1 signaling) while CD47 protects tumor cells from phagocytosis (via CD47/SIRP-alpha signaling). Targeting each of the above pathways with monoclonal antibodies has shown promise with PD-L1/PD-1 inhibition showing durable responses and extended overall survival for several approved products, whereas the molecules targeting CD47 pathway are in early clinical trials. Given that a significant number of patients are either resistant or relapse on PD-L1/PD-1 therapy, combinations with anti-CD47 antibodies are being explored. However, the expression of CD47 on many normal cells such as hematopoietic cells, red blood cells (RBCs) and platelets provides a widespread antigen sink which impacts the PK and adverse event profile of these agents. Methods: Here, we describe the generation and testing of a large panel of bispecifics with combinations of different affinities to PD-L1 and CD47 using the B-Body™ bispecific screening platform. The bispecific antibodies were screened in various in vitro activity and developability assays. Selected leads from the screen were tested in multiple in vivo models with differential expression of CD47 and PD-L1. Results: The lead bispecific antibodies showed significant blockade of SIRPa/CD47 and PD-L1/PD-1 signaling in vitro and tumor growth inhibition in vivo. The studies also showed no significant binding to RBCs and induced minimal RBC phagocytosis in vitro. A summary of screened candidates and characterization of a lead candidate being developed further will be presented. Conclusions: We have identified multiple CD47/PD-L1 bispecific antibodies with favorable efficacy and safety profiles. Selection of a lead for further IND and clinical development is underway.